The impact of micro-financing on the empowerment of women in Ghana:A Case Study of Akad Microfinance - AGYEMENG-DUAH, BENJAMIN (2016)
A thesis submitted to the School of Business, Kwame Nkrumah University of Science and Technology (Knust) in partial fulfillment of the requirements for the degree of masters in business administration, Finance option.